2022
DOI: 10.3389/fmed.2021.768101
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Triglyceride-Glucose Index for In-hospital Mortality in Patients With Severe Fever With Thrombocytopenia Syndrome: A Multi-Center Observational Study

Abstract: Background: Triglyceride-glucose (TyG) index has been proposed as a reliable indicator for insulin resistance and proved to be closely associated with the severity and mortality risk of infectious diseases. It remains indistinct whether TyG index performs an important role in predicting in-hospital mortality in patients with severe fever with thrombocytopenia syndrome (SFTS).Methods: The current study retrospectively recruited patients who were admitted for SFTS from January to December 2019 at five medical ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In Zhang et al's study that investigated 77 patients with SFTS, elevated blood glucose levels were correlated with fatal outcomes compared with survival in patients with levels in the normal range . Another study indicated that the triglyceride-glucose (TyG) index, derived from triglyceride and fasting blood glucose levels, was associated with in-hospital death in patients with SFTS ( Zhang T. et al, 2021 ). However, most of the studies were either limited to patients with diabetes or biased by insufficient numbers of patients in comparison groups.…”
Section: Introductionmentioning
confidence: 99%
“…In Zhang et al's study that investigated 77 patients with SFTS, elevated blood glucose levels were correlated with fatal outcomes compared with survival in patients with levels in the normal range . Another study indicated that the triglyceride-glucose (TyG) index, derived from triglyceride and fasting blood glucose levels, was associated with in-hospital death in patients with SFTS ( Zhang T. et al, 2021 ). However, most of the studies were either limited to patients with diabetes or biased by insufficient numbers of patients in comparison groups.…”
Section: Introductionmentioning
confidence: 99%
“…The TyG index, serving as a novel surrogate marker for insulin resistance, has been extensively utilized in predicting the risk and severity of various diseases (31). Numerous clinical investigations on the association between the TyG index and patient outcomes across diverse diseases have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the World Health Organization (WHO) listed SFTS as an infectious disease requiring urgent research and development because of its high case fatality rate and the possibility of transmission [8]. For seriously ill patients, the disease can quickly develop into multiple organ failure and eventually lead to adverse clinical outcomes [9]. Therefore, it is very important for SFTS patients to identify the high risk of adverse clinical outcome in time.…”
Section: Introductionmentioning
confidence: 99%